Moving towards personalised therapy in head and neck squamous cell carcinoma through analysis of next generation sequencing data. (March 2016) - Giefing, M.; Wierzbicka, M.; Szyfter, K.; Brenner, J.C.; Braakhuis, B.J.; Brakenhoff, R.H.; Bradford, C.R.; Sorensen, J.A.; Rinaldo, A.; Rodrigo, J.P.; Takes, R.P.; Ferlito, A.
Abstract: Personalised medicine tumour boards, which leverage genomic data to improve clinical management, are becoming standard for the treatment of many cancers. This paper is designed as a primer to assist clinicians treating head and neck squamous cell carcinoma (HNSCC) patients with an understanding of the discovery and functional impact of recurrent genetic lesions that are likely to influence the management of this disease in the near future. This manuscript integrates genetic data from publicly available array comparative genome hybridization (aCGH) and next-generation sequencing genetics databases to identify the most common molecular alterations in HNSCC. The importance of these genetic discoveries is reviewed and how they may be incorporated into clinical care decisions is discussed. Considerations for the role of genetic stratification in the clinical management of head and neck cancer are maturing rapidly and can be improved by integrating data sets. This article is meant to summarise the discoveries made using multiple genomic platforms so that the head and neck cancer care provider can apply these discoveries to improve clinical care. Highlights: HNSCC tumor sequencing has identified new pathogenic pathways and therapeutic targets. Multidisciplinary 'personalised medicine' tumour boards may radically alter HNSCC intervention. The integration of genetics data with clinical decision making requires collaboration. CCND1 and CDKN2A genomic alterations correlate with poor overall survival in HNSCC.